THE USE OF THINK INSIDE THE BOX STRATEGY TO IMPROVE STUDENTS VOCABULARY MASTERY AT SECOND GRADE STUDENTS OF SMPN 4 PRAYA BARAT DAYA - Terasne Terasne; Nanag Sugianto (JUPE : Jurnal Pendidikan Mandala, 2019)
The research is aimed to the use of think inside the box strategy be able to improve students vocabulary mastery. The subject of this study was 20 students at second grade students of SMPN 4 Praya Barat Daya. In which consist of 8 males and 12 females. It was classroom action research with two cycles, each cycles of four steps: planning, acting, observing and reflecting. The data gathering used written test, and questionnaires and analyzed by using quantitative and qualitative approach. At the result of the first cycle was failed where the mean score of pre test was 62.35 and class percentage was 30% and he mean score of post test was 70.25 and class percentage was 65% and the result of the second cycle that the mean score was 80,2 and the class percentage was 80% indicating the target of 75 of the minimum criterion has been achieved, it means that the action was stopped.